Endogenous Borders? Exploring a Natural Experiment on Border Effects - Nikolaus Wolf; Hans Christian Heinemeyer; Max-Stephan Schulze (Verein für Socialpolitik, 2010)
A large literature documents the impact of borders on trade. However, in all these studies border effects are identified from cross-sectional variation alone. We do not know the "treatment effect" of borders nor can we rule out reverse causation. In this paper we exploit the border changes imposed across Europe by the peace treaties in 1919-20 as a natural experiment. We estimate the effects of borders on trade with a difference in difference approach and find that the "treatment effects" of borders are much smaller than the pure cross-sectional effects. We find strong evidence that border changes occurred systematically along pre-existing trade frictions.
Keywords: F15; N13; N14; 330; border effects; treatment effects; European history